(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the sociolinguistic factors that drive code-switching, highlighting how these factors reflect and shape social identities, power dynamics, and communicative contexts. Key influences include identity and group membership, where language choice signals affiliation or differentiation; context and setting, which dictate the appropriateness of language use; and the topic of conversation, which may necessitate specific linguistic precision. The article also examines how social relationships and power dynamics influence language switching, with speakers adjusting their language use to reflect hierarchy, solidarity, or resistance.